Legal-normative bases of kazakh onomastics (Eurasian Journal of Philology Science and Education, 2016)
One of the problems of modern linguistics is forming the onomastic space of independent Kazakhstan and determining its national expression. Functions of onomastics and its content closely related to history, ethnography, ethnology, geography, political science, sociology, jurisprudence etc. It is known that researching in linguistics cannot investigate this problem of onomastics fully. For instance, the situation of modern Kazakhstan supposes the observance of political principles between nations and the state’s interest. In this connection, our researching of the modern condition of onomastics will be realized on the basis of normative legal documents. Lately, there are plenty of objects which are renamed by foreign names in cities. It goes to show the absence of legal system about objects’ renaming. The authors of the article examine this problem, make the analysis of normative legal documents of Kazakh onomastics, and also give improving recommendations for renaming objects.
Keywords: Kazakh onomastics; legal¬normative documents; language politics; systems of onums; forming of оnomastic spaces; national interest.